2021
DOI: 10.1021/acs.langmuir.1c00022
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Amphiphilic Copper Nanoclusters Driven by Cationic Surfactants

Abstract: Amphiphilicity is an excellent physicochemical property, which is yet to be explored from traditional surfactants to nanoparticles. This article shows that the amphiphilicity of copper nanoclusters (CuNCs) can be readily tuned by electrostatic interactions with cationic surfactants and cetyltrimethylammonium cations (CTA + ) with counterions Br − , Cl − , and C 7 H 8 O 3 S − . Due to the role of surface ligands, the complexes of glutathione-capped CuNCs (GSH-CuNCs) and the surfactants exhibit good amphiphilici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Most cubosomes used in previous studies are formed predominantly from lipids and partly from block copolymers. We pioneered the design and subsequent synthesis of heterocluster Janus molecules (HCJMs) by tethering dissimilar nanoclusters [a polyoxometalate (POM) and a polyhedral oligomeric silsesquioxane (POSS)] using different organic linkers (Figure A). We also developed an approach to self-assemble heterocluster Janus dumbbells into cubosomes with the double-diamond (DD) nanostructure owing to their amphiphilic characteristics originating from the difference in the solubility and immiscibility of the two types of clusters . They form truncated octahedra (Figure B,C) as equilibrium shapes and are constructed by a bilayer in which the POM layer is sandwiched between two POSS layers.…”
Section: Resultsmentioning
confidence: 99%
“…Most cubosomes used in previous studies are formed predominantly from lipids and partly from block copolymers. We pioneered the design and subsequent synthesis of heterocluster Janus molecules (HCJMs) by tethering dissimilar nanoclusters [a polyoxometalate (POM) and a polyhedral oligomeric silsesquioxane (POSS)] using different organic linkers (Figure A). We also developed an approach to self-assemble heterocluster Janus dumbbells into cubosomes with the double-diamond (DD) nanostructure owing to their amphiphilic characteristics originating from the difference in the solubility and immiscibility of the two types of clusters . They form truncated octahedra (Figure B,C) as equilibrium shapes and are constructed by a bilayer in which the POM layer is sandwiched between two POSS layers.…”
Section: Resultsmentioning
confidence: 99%
“…An attempt has been made to disperse this molecule in water by encapsulating it into the hydrophobic core of a micelle. CTAB is a well-known cationic surfactant 64 and it forms micelles with a hydrophobic core in the water medium. 65 In the absence of CTAB, it is not possible to disperse the N1 in water as indicated by the colorless appearance of the water phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pd NCs and PdS NCs self-assemble into rhombic/hexagonal platelet-like structures ( Figure 8 B) [ 87 ]. Hao et al, in their study, showed an enhancement of fluorescence intensity with the formation of self-assembled amphiphilic Cu NCs [ 88 ]. The amphiphilic complex of GSH-capped Cu NCs was prepared by electrostatic interaction and then assembled in an aqueous solution in the presence of a surfactant by rearranging the surface ligands.…”
Section: Nanoscale Forces On Assemblymentioning
confidence: 99%